2022
DOI: 10.18592/alhadharah.v21i1.6253
|View full text |Cite
|
Sign up to set email alerts
|

Cadar dan Tantangan Sosial: Studi Fenomenologi atas Kewajiban Penggunaan Cadar bagi Santriwati Ma`hadal Ulum Diniyah Islamiyah Bireuen Aceh

Abstract: This study aims to identify the internalization process and social challenges regarding the mandatory use of the veil for the Dayah (Pesantren) Ma'hadal 'Ulum Diniyah Islamiyah (MUDI) students of the Samalanga Grand Mosque, Bireuen Regency, Aceh Province. This study uses a symbolic interactionism theory approach from George Herbert Mead. The results showed that the use of the veil for Dayah MUDI students contained the meaning of the identity symbol of Islamic teachings in totality (kāffah), preventive actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to Mead in his concept of "self" the individual can internalize experiences so that they have an effect on their actions as well as put themselves the same as objects. Thus, the individual can also calculate the benefits for himself (Azizi et al 2022). Almost in line with Blumer's thinking (Niadi et al 2023) The theory of symbolic interactionism emphasizes behavioristic where the interaction carried out by the individual affects the meaning and behavior of a person.…”
Section: Post-normalization Ecological Impactmentioning
confidence: 93%
“…According to Mead in his concept of "self" the individual can internalize experiences so that they have an effect on their actions as well as put themselves the same as objects. Thus, the individual can also calculate the benefits for himself (Azizi et al 2022). Almost in line with Blumer's thinking (Niadi et al 2023) The theory of symbolic interactionism emphasizes behavioristic where the interaction carried out by the individual affects the meaning and behavior of a person.…”
Section: Post-normalization Ecological Impactmentioning
confidence: 93%
“…Da'wah bil hal Veil trendy also invites women to implement Islamic values in everyday life. (Azizi et al, 2022) Based on the data found in the field, it can be concluded that there are several reasons why a Muslim woman chooses to wear a trendy veil which can be seen in the table below. The desire to look beautiful and attractive is the nature of a woman, but even so, she does not want to violate the Sharia.…”
Section: The Understanding Of Veil Trendymentioning
confidence: 99%